Using the care processes construct of McCormack and McCance's person-centred framework to critically analyse nursing care delivered: a case study. (2nd December 2022) - Guthrie, Lauren; Reid, Bernie
Abstract : This paper uses a case study approach to critically analyse nursing care provided for a patient living with dementia in an older persons' care ward, using two care processes from the person-centred framework: working with patients' beliefs and values, and shared decision making.